EVALUASI FISIK RANSUM LENGKAP BERBENTUK WAFER BERBAHAN BAHAN UTAMA JERAMI JAGUNG DAN BIOMASSA MURBEI (Physical Evaluation of Complete feed Wafer formulated Using Corn Straw and Mulberry Biomass as the main Ingredients) - S. Syahrir; M. Z. Mide; Harfiah Harfiah (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2017)
Mulberry biomass has potential ruminant feed quality due to its potential for the production and content of nutrients, but its utilization as feed is still diffcult to fnd. The residual of agriculture also has considerable potential as a source of ruminant feed. The combination of agriculture byproducts such as corn straw and the mulberry biomass into a complete ration in form of wafer is an effective alternative for producing complete feed. The ration was formulated into a complete ration in the form of wafers (wafer complete feed) which was characterized by a quality suffcient nutrient content and a compact form of the product. To complement the availability of nutrients, improve both physical quality and palatability, the complete feed wafer was formulated using such raw materials as corn straw, mulberry biomass, concentrate, and molasses. This purpose of this study was to evaluate the physical properties of wafer complete feed. The study was carried out according to completely randomized design (CRD) consisted of six treatments and four replications for each treatment. The amount of complete feed formulated for each treatment was 1000 g dry matter basis with diameter of 21 cm. The physical properties of complete feed formula were evaluated based on the density value, water absorption, and rupture test (crushing test). The best result in formulating complete feed wafer was obtained by using a combination of 5 - 10 % molasses with 25 - 30% mulberry biomass.